PERTANGGUNGJAWABAN KEUANGAN PONDOK PESANTREN: STUDI PADA YAYASAN NAZHATUT THULLAB - Arifin, Zainal (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to comprehend how the financial management of Nazhatut Thullad boarding school. Moreover, to comprehend how the financial management of Nazhatut Thullab foundation in presenting financial statement based on accounting standard. The source of data has been obtained directly from its source in the form of unstructured interview to the foundation management party and the documentation of data is in the form of 2012 financial statement of Nazhatut Thullab foundation. The result of the research shows that: 1) accounting media that has been used in the financial management responsibility of Nazhatut Thullab boarding school is cash receipt and cash disbursement report; 2) the source of funds of the foundation is obtained from apprentices, and donation either from the government or the community; 3) Nazhatut Thullab boarding school has not presented its financial statement which is based on Accounting Standard Statement Number 45 about nonprofit entity.Keywords: Responsibility, Foundation Financial Management, and Financial Statement